Fishhook characteristics of biodiesel lubricity during autoxidation. (1st January 2023) - Zheng, Yuzeng; Li, Fashe; Zhang, Huicong; Wang, Shuang; Zhao, Zhongjin; Wang, Wenchao; Chen, Renyi
Highlights: The trend of grinding spot diameter for biodiesel during storage is like a fishhook. Biodiesel decomposed to small molecules and then aggregated into macromolecules. Coagulation point and kinematic viscosity of biodiesel increased by 1 °C and 8.8% during storage. The friction coefficient and force of biodiesel increased by 50% and 60%. Abstract: The effects of light, ventilation and antioxidant on biodiesel performance and the corresponding influence mechanisms are investigated during long-term storage. The biodiesel exhibits slow autoxidation and its physical/chemical properties change during storage. Light and ventilation conditions can accelerate the oxidation of biodiesel, thereby aggravating its degradation. During the autoxidation process of biodiesel, the grinding spot diameter firstly decreases from 165.01 μm to 131.45 μm and then increases to 362.5 μm, similar to the shape of a fishhook. During the initial storage stage, the fatty acid methyl ester in biodiesel is decomposed into carboxylic acid and small molecular substances such as aldehydes and ketones, thereby improving the lubricity of biodiesel and reducing the grinding spot diameter. After long-term storage, insoluble resins and sediments are generated, causing an increase in the grinding spot diameter. Specifically, the kinematic viscosity of biodiesel is increased to 4.407 mm 2 /s even under dark and sealed storage conditions.